Stigmas toward psychosis‐related clinical features among the general public in Taiwan - Wang, Yen‐Chin; Lin, Yi‐Ting; Liu, Chih‐Min; Hwang, Tzung‐Jeng; Hsieh, Ming H.; Chien, Yi‐Ling; Hwu, Hai‐Gwo; Liu, Chen‐Chung (Asia-Pacific psychiatry, 2020)
Introduction Stigma can be a barrier to early intervention of severe mental illnesses, especially schizophrenia, which further leads to poor outcomes. Mental health campaigns were designed to educate the general public about signs for early identification of psychosis, but the line between schizophrenia and attenuated psychosis was not well demarcated. We wonder if people would generalize their stigmas towards schizophrenia to subjects with subthreshold psychotic symptoms. Methods A cross‐sectional survey was employed which used a structured questionnaire, comprised of four case vignettes describing attenuated psychosis syndrome (APS), schizophrenia, psychotic‐like experiences (PLE), or depression, and was followed by two sets of questions using the 4‐point Likert scale to measure discrimination and prejudices. Participants were chosen by convenience sampling of laypersons from different backgrounds. Results A total of 268 subjects completed this survey. A gradient of stigmas, highest toward schizophrenia, followed by APS/depression, and lowest toward PLE was apparent across gender, all age groups, and education levels. Participants who were younger and had higher education revealed a trend of lower prejudice and discrimination. People who have visited a psychiatric hospital showed higher discrimination toward schizophrenia, APS, and depression. People who have seen mentally ill persons in public places showed lower stigma toward PLE. Discussion Our respondents posed a differentiable attitude towards PLE, APS, and schizophrenia, while exhibiting no difference between APS and depression. Certain personal attributes were correlated with stigma levels. Further investigation about mental health literacy and attitudes towards subjects with psychotic symptoms in the general public is warranted.